Leucine‐rich repeat‐containing G‐protein‐coupled receptor 5 expression and clinicopathological features of colorectal neuroendocrine neoplasms. Issue 8 (24th July 2018) - Nakajima, Tomoyuki; Uehara, Takeshi; Kobayashi, Yukihiro; Kinugawa, Yasuhiro; Yamanoi, Kazuhiro; Maruyama, Yasuhiro; Suga, Tomoaki; Ota, Hiroyoshi
Abstract : LGR5 is expressed in various tumors and has been identified as a putative intestinal stem cell marker. Here we investigated LGR5 expression in colorectal neuroendocrine neoplasms and analyzed the correlation with pathological characteristics. We evaluated the clinicopathological features of 8 neuroendocrine tumor (NET) grade 1 (NET G1), 4 NET Grade 2 (NET G2), and 8 NET Grade 3 (NET G3; also termed neuroendocrine carcinoma, or NEC) cases. We examined LGR5 expression using an RNAscope, a newly developed RNA in situ hybridization technique, with a tissue microarray of the neuroendocrine neoplasm samples. LGR5 staining in individual tumor cells was semi‐quantitatively scored using an H‐score scale. We also performed a combination of LGR5 RNA in situ hybridization and synaptophysin immunohistochemistry. All cases contained tumor cells with some LGR5 ‐positive dots. For all cases, H‐scores showed a positive correlation with nuclear beta‐catenin expression. In the NEC group, there was a strong positive correlation between H‐score and beta‐catenin expression. Our findings suggest that LGR5 may serve as a stem cell marker in NEC, as is the case in colon adenocarcinoma. The positive correlation between H‐score and beta‐catenin expression suggests that LGR5 expression might be affected by beta‐catenin expression in neuroendocrine neoplasms and especially in NEC.